The Legacy of Sexual Ancestors in Phenotypic Variability, Gene Expression, and Homoeolog Regulation of Asexual Hybrids and Polyploids - Bartoš, Oldřich; Röslein, Jan; Kotusz, Jan; Paces, Jan; Pekárik, Ladislav; Petrtýl, Miloslav; Halačka, Karel; Štefková Kašparová, Eva; Mendel, Jan; Boroń, Alicja; Juchno, Dorota; Leska, Anna; et al. (Molecular biology and evolution, 2019)
Hybridization and polyploidization are important evolutionary processes whose impacts range from the alteration of gene expression and phenotypic variation to the triggering of asexual reproduction. We investigated fishes of the Cobitis taenia-elongatoides hybrid complex, which allowed us to disentangle the direct effects of both processes, due to the co-occurrence of parental species with their diploid and triploid hybrids. Employing morphological, ecological, and RNAseq approaches, we investigated the molecular determinants of hybrid and polyploid forms. In contrast with other studies, hybridization and polyploidy induced relatively very little transgressivity. Instead, Cobitis hybrids appeared intermediate with a clear effect of genomic dosing when triploids expressed higher similarity to the parent contributing two genome sets. This dosage effect was symmetric in the germline (oocyte gene expression), interestingly though, we observed an overall bias toward C. taenia in somatic tissues and traits. At the level of individual genes, expression-level dominance vastly prevailed over additivity or transgressivity. Also, trans-regulation of gene expression was less efficient in diploid hybrids than in triploids, where the expression modulation of homoeologs derived from the "haploid" parent was stronger than those derived from the "diploid" parent. Our findings suggest that the apparent intermediacy of hybrid phenotypes results from the combination of individual genes with dominant expression rather than from simple additivity. The efficiency of cross-talk between trans-regulatory elements further appears dosage dependent. Important effects of polyploidization may thus stem from changes in relative concentrations of trans-regulatory elements and their binding sites between hybridizing genomes. Links between gene regulation and asexuality are discussed.
Keywords: cis-/trans-regulation; Hybridization, Genetic; tissue-specific gene expression; regulace genové exprese; Ecosystem; Female; Phenotype; zvířata; hybridizace genetická; máloostní; Cypriniformes; expression-level dominance; ženské pohlaví; Gene Expression Regulation; Male; fenotyp; asexuality; Reproduction, Asexual; Animals; hybridization; mužské pohlaví; polyploidie; Polyploidy; nepohlavní rozmnožování; ekosystém; polyploidy